2011
DOI: 10.1038/jp.2011.17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cerebrovascular dysautoregulation and arterial blood pressure in the premature infant

Abstract: Objective: To evaluate cerebrovascular autoregulation as a function of arterial blood pressure (ABP) in the critically ill, premature infant.Study Design: A prospective observational pilot study was conducted in two tertiary care Neonatal Intensive-Care Units. Premature infants (n ¼ 23, p30 weeks estimated gestational age with invasive ABP monitoring) were enrolled and received routine care while undergoing continuous autoregulation monitoring, using the cerebral oximetry index (COx). The COx is a moving, line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 28 publications
6
88
2
1
Order By: Relevance
“…We recently demonstrated that the initiation of high V T ventilation for the first 15 min after birth caused large fluctuations in CBF (Figure 3), impaired cerebral autoregulation (cerebral vasoparalysis), and increased vascular extravasation (leakage), a precursor to cerebral hemorrhage (4). Abnormal fluctuations in CBF (defined as prolonged swings in CBF, either high or low, for more than 10-20 s) are common in preterm infants (37) and occur as a result of adverse pulmonary, cardiovascular, or systemic (vascular) factors. The majority of abnormal CBF is due to impaired cardiovascular control (38).…”
Section: Hemodynamic Consequences Of the Initiation Of Positive Pressmentioning
confidence: 99%
“…We recently demonstrated that the initiation of high V T ventilation for the first 15 min after birth caused large fluctuations in CBF (Figure 3), impaired cerebral autoregulation (cerebral vasoparalysis), and increased vascular extravasation (leakage), a precursor to cerebral hemorrhage (4). Abnormal fluctuations in CBF (defined as prolonged swings in CBF, either high or low, for more than 10-20 s) are common in preterm infants (37) and occur as a result of adverse pulmonary, cardiovascular, or systemic (vascular) factors. The majority of abnormal CBF is due to impaired cardiovascular control (38).…”
Section: Hemodynamic Consequences Of the Initiation Of Positive Pressmentioning
confidence: 99%
“…Soul et al found impaired cerebrovascular autoregulation in about 20% of the recording time using NIRS in 87 out of 90 very preterm infants during the first 5 days after birth [29]. Other studies also reported on fluctuating autoregulation impairment during the first days after birth [6,[30][31][32][33].…”
Section: Autoregulatory Capacitymentioning
confidence: 90%
“…Munro et al reported that the lower threshold in MABP for cerebrovascular autoregulation, measured by NIRS, might be at 29 mmHg for preterm infants with a GA ranging from 23 to 30 weeks [46]. Other studies were not able to define a clear lower threshold for their cohorts but used a large change in magnitude or percentage of time of impaired cerebrovascular autoregulation to define dangerous MABP levels [29,30]. In contrast, Binder et al found that a 1-h hypotensive episode (defined as an MABP below the infant's GA) did not affect NIRS rSO 2 significantly in preterm infants with a GA <37 weeks [47].…”
Section: Autoregulation Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations